Numerical Simulation of the Gas-Liquid Flow Inside a Horizontal Static Mixer - Ryan Anugrah Putra; Akhlisa Nadiantya Aji Nugroho (Jurnal Inotera, 2020)
The gas-liquid flow inside a horizontal static mixer was numerically investigated by using Euler-Euler Computational Fluid Dynamics (CFD) simulations. The results confirm that the liquid superficial velocity plays a significant role on the mixing behavior of the gas and liquid. The mixing behavior in this present study at a liquid superficial velocity of 0.2 m/s was the worst both axially and radially. Increasing the liquid superficial velocity significantly improve the mixing between gas and liquid. However, the unwanted gas layer still can be found at the superficial liquid velocity less than 0.8 m/s. A good mixing behavior in this study was achieved at a relatively high velocity (i.e. larger than 0.8 m/s).